A modeling study of visibility in the Grand Canyon - Weissbluth, Michael Jeffrey, author; Cox, Stephen K., author; Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 1986)
Using a backward version of the Monte Carlo Radiative Transfer model, radiance values in the Grand Canyon were simulated to within the precision of ten percent. The contiguous spectral contrast was introduced to distinguish between adjacent areas of the same target and compared to the apparent spectral contrast. The contiguous spectral contrast is a valuable tool in evaluating visibility because in some cases, the target became more distinguishable when viewed against the sky while the target features became less distinguishable. Average equilibrium radiance values were calculated and incorporated into the Koschmieder estimate; the Koschmieder estimate was deemed to be of limited value in the Grand Canyon because of the violation of the assumptions used to derive the estimate. It was shown that first order scattering results alone could be used to estimate apparent spectral contrast to within a 10% accuracy; higher order scattering must be considered when radiance values are calculated for the Grand Canyon scene.
August 1986.
Keywords: Meteorological optics -- Arizona -- Grand Canyon